Well-Differentiated Thyroid Cancer Invading the Trachea in a Pediatric Patient - Nicole Mott, BS (AACE Clinical Case Reports, 2021)
Objectives: Pediatric thyroid cancer is rare. Most cases are well-differentiated thyroid cancers (WDTCs). However, gross laryngotracheal invasion of WDTCs is unusual. This report details the first case in English medical literature of a pediatric WDTC invading the trachea. Methods: Thyroid stimulating hormone, free triiodothyronine, free thyroxine, thyroglobulin, parathyroid hormone, calcitonin, thyroglobulin antibody, chest magnetic resonance imaging, neck ultrasound, neck computed tomography, and fine needle aspiration were performed. Results: A 9-year-old boy with moderate persistent asthma presented with increasing upper respiratory symptoms. Spirometry suggested a fixed upper airway obstruction. Chest x-ray revealed a left tracheal shift, and chest magnetic resonance imaging identified a right thyroid mass. Thyroglobulin level was 809 ng/mL (normal, ≤33 ng/mL). Results of thyroid stimulating hormone, free triiodothyronine, free thyroxine, parathyroid hormone, calcitonin, and thyroglobulin antibody were normal. Neck ultrasound revealed 2 right thyroid lobe nodules. Neck computed tomography revealed tracheal compression. Fine needle aspiration of the largest nodule yielded atypia of undetermined significance. Bronchoscopy findings at his local hospital were concerning for tracheal invasion. He underwent total thyroidectomy, cricotracheal resection, reconstruction, and radioactive iodine therapy (220 mCi). Pathology demonstrated a well-differentiated papillary thyroid carcinoma without solid or diffuse sclerosing subtype components. Tumor cytogenetic and single nucleotide polymorphism microarray studies showed normal findings. One year postoperatively, neck ultrasound demonstrated no recurrence, and thyroglobulin levels were undetectable while on levothyroxine therapy. Conclusion: Pediatric WDTC invading the trachea has not been reported.